Column Profile Maps: A Tool for the Design and Analysis of Complex Distillation Systems - Holland, Simon Thornhill (My University, 2006)
Techniques for the design and analysis of simple column separations are well established. Shortcut design techniques have been employed in the initial design of these “traditional” distillation systems for a number of years and these columns are well understood. However, few currently available techniques are useful in the design of novel or complex configurations. The techniques that are available tend to be configuration specific. An all inclusive or universal, design and analysis tool, that can be applied to any and all configurations, is required. Tapp et al (2004) introduced Column Profile Maps (CPMS) as a means of addressing this issue. These are maps of composition profiles for column sections with defined net-molar-flow and reflux ratio. It is suggested that by producing CPMs for a configuration a designer can essentially superimpose these, determine feasible operating profiles and hence column operating parameters. In this thesis we show that this technique can be used to, not only produce quick and easy complex column designs but gain a comprehensive understanding of the steady-state operation of these arrangements. We demonstrate this analytical potential first by application of the CPM technique to the two-product feed distribution problem. It is shown that feed distribution can lower the minimum required reflux ratio for non-sharp separations and in some cases produce feasible separations from previously infeasible product specifications. A composition region of operation for all distributed feed policies is also found. The potential for detailed analysis, design and optimisation of complex configurations is demonstrated via application of the CPM procedure to the fully thermally coupled (Petlyuk) distillation column at both sharp and non-sharp split conditions. A detailed design methodology for any configuration results from this. It is found that the Petlyuk column can operate under five possible bulk/net flow conditions and that very interesting and counter-intuitive net-molar-flows are possible. A feasible column parameter region equivalent to the optimality region (Halvorsen and Skogestad, 2001) is found for zeotropic systems. Importantly a minimum reflux condition for the Petlyuk column is found. This condition can be applied to all zeotropic systems for all product specifications. It is also demonstrated that the CPM technique can be used for design optimisation of separation systems.
Student Number : 9510423G PhD Thesis School of Chemical and Metallurgical Engineering Faculty of Engineering and the Built Environment
Keywords: distillation; column profile maps; petlyuk; difference point equation; distributed feed; complex distillation configurations; separtion synthesis